PERUBAHAN KEWENANGAN KONKUREN PEMERINTAH DAERAH BIDANG TATA RUANG PASCA TERBITNYA UU CIPTA KERJA - Faridatul Fathnil Harbiyah (2022)
The preparation of this Legal Memorandum has a problem formulation with the background that the concurrent authority of the government is a government affair which includes central affairs as well as regional affairs. This matter is divided into two, namely mandatory government affairs and optional affairs. Mandatory government affairs itself consists of two types, namely mandatory affairs related to basic services and optional affairs not related to basic services, which in this spatial arrangement are included in mandatory affairs related to basic services. So that a change in the authority of the regional government affects the implementation of the regional government which results in the absence of legal certainty in spatial planning permits. The results of this paper can be concluded as follows, the issuance of the Job Creation Law has resulted in fear of the absence of legal certainty and has implications for the administration of regional government, especially in spatial planning. Withdrawal of local government authority into the authority of the central government makes the central government have the greatest authority so that it can cause new problems if it does not have the ability to read policies in each region in Indonesia.